1994
DOI: 10.1093/ije/23.5.931
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and the Risk of Acute Myocardial Infarction in a Gulf Arab Population

Abstract: There is scope for lifestyle change in reducing AMI risk, by changes in physical activity, smoking and dietary habits. In addition, measures to control hypertension and diabetes should be given a high priority in any national health policy to prevent AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Al-Roomi et al101 conducted a case-control study of lifestyle factors associated with acute myocardial infarction in adults aged 20–79 years in Bahrain. After adjusting for several demographic and health variables, the odds of having a first myocardial infarction in subjects with an infrequent intake of fruit (<3 times/week) was 1.57 (95% CI 0.61–2.53) and in those with an infrequent intake of vegetables (<3 times/week) was 1.40, (95% CI 0.77–2.52), with both rates being higher than in control subjects.…”
Section: Factors Associated With N-ncds In Emrmentioning
confidence: 99%
“…Al-Roomi et al101 conducted a case-control study of lifestyle factors associated with acute myocardial infarction in adults aged 20–79 years in Bahrain. After adjusting for several demographic and health variables, the odds of having a first myocardial infarction in subjects with an infrequent intake of fruit (<3 times/week) was 1.57 (95% CI 0.61–2.53) and in those with an infrequent intake of vegetables (<3 times/week) was 1.40, (95% CI 0.77–2.52), with both rates being higher than in control subjects.…”
Section: Factors Associated With N-ncds In Emrmentioning
confidence: 99%
“…Life expectancy is increasing and the majority of the aged population will be living in the developing countries by 2025 [22] . The increase in the prevalence of wellestablished risk factors for vascular disease (smoking, obesity, inactivity, diabetes and hypertension), better health care along with increasing age of the population may increase stroke incidence [23,24] . Like in the developed countries, stroke remains a major public health problem in the GCC countries [25] .…”
Section: Introductionmentioning
confidence: 99%
“…Chronic diseases, and smoking-related diseases in particular, have become the main health problems in the Arab Gulf states, including Bahrain (Al-Owaish & Zack, 1982;Al-Roomi, Musaiger, & Al-Awadi, 1994;Al-Tamimi et al, 1996;Hamadeh, 1987;Hamadeh, & McPherson, 1993;Magrath & Litvak, 1993;Musaiger, 1994). Studies have shown that the prevalence of smoking in some of these countries is reaching an alarming level, especially in men (WHO, 1996).…”
Section: Introductionmentioning
confidence: 99%